Considerations on the role of teacher autonomy - Cárdenas Ramos, Rosalba (Colombian Applied Linguistics Journal, 2006)
This article aims at analyzing what is involved in teacher autonomy and why it is of paramount importance to understand, develop, and experience autonomy as teachers in order to be able to guide our students in the development of autonomous behaviors as language learners and life-long learning individuals.